Pelayanan Dan Pengawasan Terhadap Pelintas Batas Di Pos Lintas Batas Darat Mota’ain Perbatasan Negara Indonesia – Timor Leste - Sahudiyono Sahudiyono; Fraquelino Pinto (Sekolah Tinggi Maritim Yogyakarta, 2019)
The decision of East Timor to separate itself from Republic Of Indonesia and become independent on May 20th ,2002 remain an unsolved problem between the two countries. The existing problem lies in the borders between the two nations which is divided into two borders such as maritime and on-shore border. On of the on-shore border is Atambua regency in east Nusa Tenggara. Some problems which may occur in that region are drug and weapon smuggling, fuel smuggling, Passport and Visa abuse, human trafficking. This research is aimed to identify and comprehend immigration services in the borders of the two nations as well as the problems due to the law violation that may occur including the triggering motives in the borders of those two countries. The type of the research is descriptive qualitative by taking data using observation and random interview toward those living nearby the border line and toward some immigration officers in the Atambua border line. The result of the research showed that first, in fact Indonesian government had given good services as well as good supervision toward passersby in the border of the two nations, however, there were still many weaknesses due to the facilities and the quality and quantity of human resources. Second, there were still found many problems in economics, socio cultural, and politic affairs which lead to the violations toward immigration law and others conducted by both Indonesian citizens and East Timor citizen. Some of those violations were such as abuse of immigration documents, smuggling, drug abuse, and another crimes. Third, It is recommended that the cooperation and collaboration among institutions both in the center and regional level of Indonesia as well as cooperation between Indonesian government and East Timor government should be increased.